Desain Tungku Biomassa pada Sistem Pengering Erk-Hibrid untuk Pengeringan Benih Jarak Pagar - Muh. Tahir; Wahyu Purnama (PERTETA, 2010)
Abstract This research was designing a unit of biomass stove which was rising heat used on greenhouse effect dryer system. The heat of drying system then utilized to dry seed with a certain Celsius degree; average of 40 oC and constantly due to effect of temperature controller. The result of the designed system indicated that level of castor oil plant drying temperature was 38 - 41 oC. The stove’s efficiency to the heat exchanger had 74.0 % and the efficiency of heat exchanger to the drying system had 57,3 %. The viability testing of castor oil plant seed which had been drying yield 90 % growing showed the ability to reduce dormant. Another treatment of the seed to remain into water for 6 hours before planted is not suggested.Keywords: Stove, dryer, seed, dormant, castor oil plantDiterima: 24 Juli 2009; Disetujui: 25 Januari 2010